On a characteristic initial value problem in plasma physics - Calogero, Simone Carmelo (2006)
The relativistic Vlasov-Maxwell system of plasma physics is considered with initial data on a past light cone. This characteristic initial value problem arises in a natural way as a mathematical framework to study the existence of solutions isolated from incoming radiation. Various consequences of the mass-energy conservation and of the absence of incoming radiation condition are first derived assuming the existence of global smooth solutions. In the spherically symmetric case, the existence of a unique classical solution in the future of the initial cone follows by arguments similar to the case of initial data at time $t=0$. The total mass-energy of spherically symmetric solutions equals the (properly defined) mass-energy on backward and forward light cones.